2010
DOI: 10.1029/2009jd013772
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the phase‐locked 2 day wave over the Australian sector using medium‐frequency radar and airglow data

Abstract: [1] The quasi 2 day wave, with a nominal mean period just above 50 h, is a significant feature of the 80-100 km altitude region in both hemispheres. It becomes particularly prominent in the Southern Hemisphere summer at midlatitudes where, a short time after summer solstice, its amplitude rapidly increases and its mean period is found to be approximately 48 h, producing an oscillation phase locked in local time. This lasts for a few weeks. Presented here are observations of the meridional winds and airglow ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 34 publications
(70 reference statements)
7
56
0
Order By: Relevance
“…Figure 7b,c shows the amplitude and phase of the NS winds filtered with a bandpass between 40 and 60 h, with the phase referenced to an oscillation with a period of 48 h. In general, the increase of phase with time indicates a period less than 48 h, but the steady phase observed between about day 21 and 29 shows the period at this time was close to 48 h. The same behaviour was observed Walterscheid and Vincent (1996). Studies of radar and airglow emissions from the MLT by Hecht et al (2010) corroborated the phase-locking mechanism. They found the airglow intensity response was much larger than what would be expected from the airglow temperature response, suggesting that the QTDW is causing a significant composition change, possibly due to minor constituent transport.…”
Section: The Quasi-two-day Wave and Its Impact On The Mltsupporting
confidence: 51%
“…Figure 7b,c shows the amplitude and phase of the NS winds filtered with a bandpass between 40 and 60 h, with the phase referenced to an oscillation with a period of 48 h. In general, the increase of phase with time indicates a period less than 48 h, but the steady phase observed between about day 21 and 29 shows the period at this time was close to 48 h. The same behaviour was observed Walterscheid and Vincent (1996). Studies of radar and airglow emissions from the MLT by Hecht et al (2010) corroborated the phase-locking mechanism. They found the airglow intensity response was much larger than what would be expected from the airglow temperature response, suggesting that the QTDW is causing a significant composition change, possibly due to minor constituent transport.…”
Section: The Quasi-two-day Wave and Its Impact On The Mltsupporting
confidence: 51%
“…Several past observational and modeling studies have found strong evidence for various tidal/planetary wave interactions, including the generation of nonmigrating tides through interaction between the stationary planetary wave 1 (PW1) and the migrating diurnal tide [ Hagan and Roble , 2001; Lieberman et al , 2004; Liu et al , 2007], PW1 and the migrating semidiurnal tide [ Angelats i Coll and Forbes , 2002; Chang et al , 2009], as well as between the tides and various propagating planetary waves [ Walterscheid and Vincent , 1996; Pancheva et al , 2002; Palo et al , 2007; Hecht et al , 2010; McCormack et al , 2010]. Numerical experiments performed in these studies [ Hagan and Roble , 2001; Angelats i Coll and Forbes , 2002; Liu et al , 2007; Chang et al , 2009] have resolved wave and tidal components that could be generated only as a result of a nonlinear planetary wave/tidal interaction, while observations indicated child wave components and tidal amplitude fluctuations whose time variation closely followed that of the interacting planetary wave in the regions where the tide was dominant [ Pancheva et al , 2002; Lieberman et al , 2004; Palo et al , 2007; Chang et al , 2009; Hecht et al , 2010; McCormack et al , 2010].…”
Section: Introductionmentioning
confidence: 99%
“…The 2 day wave is important in the dynamics of the middle atmosphere because it is known to strongly interact with atmospheric tides and to modulate their amplitude [e.g., Teitelbaum and Vial , 1991; Mitchell et al , 1996; Palo et al , 1999; Pancheva et al , 2004; Wu et al , 2008]. Further, there is evidence that the 2 day wave can become phase locked to the migrating semidiurnal and diurnal tides (i.e., have a period of exactly 48 h) and through interaction with them generate a diurnal zonal wave number 6 feature and lead to rapid amplification of the 2 day wave amplitude [e.g., Walterscheid and Vincent , 1996; Hecht et al , 2010; McCormack et al , 2010]. Interactions with tides can also act to constrain 2 day wave amplitudes and results in a cascade of variance to smaller scales within the atmosphere [ Salby and Callaghan , 2008].…”
Section: Introductionmentioning
confidence: 99%